Pengaruh Model Pembelajaran Arias (Assurance, Relevance, Interest, Assesment, Satisfaction) Terhadap Kemampuan Menulis Teks Ulasan Film Siswa Kelas VIII SMPN 2 Galang - Ridha Annisa Rangkuti; Frinawaty Lestarina Barus (FKIP, Universitas Palangka Raya, 2024)
The research objective was to investigate the impact of the ARIAS (Assurance, Relevance, Interest, Assessment, Satisfaction) learning model on the ability of Grade VIII students at Galang 2 Public Middle School in writing film review texts. The population consists of 154 students in class VIII, with a sample of 30 people divided into the control and experimental groups. Researchers used the experimental method with a true experimental design and a quantitative approach. The instrument used is the essay test. The results explain 1) the ability to write film review texts for class VIII-C students (control group) at SMPN 2 Galang using conventional methods has a very low success rate, namely 52.63% of 30 students. 2) In contrast, the ability to write film review texts for class VIII-A students (experimental group) at SMPN 2 Galang using the ARIAS model has a very good success rate, reaching 91.93% of 30 students. In other words, the value of the ability to write film review text in the experimental group is greater than the control group. 3) The results of statistical analysis show that the calculated t value is 9.170 and the t table value is 1.67155. Because t count is higher than t table (9.170 > 1.67155), it can be concluded that the null hypothesis (Ho) is rejected and (Ha) is accepted. This means that the use of the ARIAS learning model has a significant effect on the ability to write film review texts for Grade VIII students at SMPN 2 Galang.